2015
DOI: 10.1002/jssc.201500539
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of “dummy” l‐phenylalanine molecularly imprinted microspheres by using ionic liquid as a template and functional monomer

Abstract: In this study, dummy imprinting technology was employed for the preparation of l-phenylalanine-imprinted microspheres. Ionic liquids were utilized as both a "dummy" template and functional monomer, and 4-vinylpyridine and ethylene glycol dimethacrylate were used as the assistant monomer and cross-linker, respectively, for preparing a surface-imprinted polymer on poly(divinylbenzene) microspheres. By the results obtained by theoretical investigation, the interaction between the template and monomer complex was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…For example, as shown in Figure D, Li et al have prepared a novel l ‐Phe MIPs using 1‐butyl‐3‐vinylimidazolium α‐aminohydrocinnamic acid salt ([Vbim][Phe]) as dummy template. The binding experiment showed that the obtained l ‐Phe MIPs possessed high bind capacity of 280.18 µmol g −1 and imprinting factor of 3.17, which was attributed to the formed ion‐pairs between imidazolium and l ‐phenylalanine in the dummy template …”
Section: Biological Molecular Imprinting With Different Scalementioning
confidence: 99%
See 1 more Smart Citation
“…For example, as shown in Figure D, Li et al have prepared a novel l ‐Phe MIPs using 1‐butyl‐3‐vinylimidazolium α‐aminohydrocinnamic acid salt ([Vbim][Phe]) as dummy template. The binding experiment showed that the obtained l ‐Phe MIPs possessed high bind capacity of 280.18 µmol g −1 and imprinting factor of 3.17, which was attributed to the formed ion‐pairs between imidazolium and l ‐phenylalanine in the dummy template …”
Section: Biological Molecular Imprinting With Different Scalementioning
confidence: 99%
“…Copyright 2016, Elsevier; D) a new IL‐based MIP was prepared by ion‐pair dummy template imprinting, which confined the charged monomer in the imprinting cavities. Reproduced with permission . Copyright 2015, Royal Society of Chemistry.…”
Section: Biological Molecular Imprinting With Different Scalementioning
confidence: 99%
“…When cells reach their proliferative limit, they start displaying signs of ageing such as large flat morphology, increased granularity, and a vacuole-rich cytoplasm. They also show increased intrinsic fluorescence which is caused by the accumulation of oxidatively damaged proteins and lipids and senescence-associated ß-galactosidase activity [38]. This growth arrested metabolically active state is known as senescence.…”
Section: Low Glucose Availability Instigate Senescencementioning
confidence: 99%
“…Previously , we have reported a strategy for the recognition of l‐ Phe by ion‐pair dummy template imprinting, which creates an imprinted polymer, using 1‐butyl‐3‐vinylimidazolium α‐aminohydrocinnamic acid salt as the template and functional monomer. The interactions between the functional monomer and template are improved by theoretical and chromatographic methods.…”
Section: Introductionmentioning
confidence: 99%